2017
DOI: 10.1038/s41598-017-05751-w
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and clustering of cardiovascular risk factors in the Chinese adult population

Abstract: Hyperuricemia is common in China and the relevance of hyperuricemia and cardiovascular disease (CVD) risk has been highlighted, but to date there has been rarely nation-wide study in China. Here, we aim to estimate the current prevalence of hyperuricemia and evaluate the associations between hyperuricemia and cardiovascular risk factors (CRFs) clustering in a large sample of China adults including a plurality of ethnic minorities. Generally, a nationally representative sample of 22983 adults aged ≥18 years was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 42 publications
3
53
0
2
Order By: Relevance
“…However, hyperuricemia is a pathological entity that is characterized by blood uric acid values beyond upper limits that has been largely associated with metabolic syndrome and increased cardiovascular risk [8][9][10]. In this sense, a recent study conducted in 22,983 Chinese adults demonstrated that subjects with hyperuricemia had higher prevalence of cardiovascular risk factors, such as dyslipidemia, hypertension, and type 2 diabetes (T2D), than individuals with normal uric acid values [11]. It is also worth mentioning that uric acid concentration associated directly with the number of cardiovascular risk factors; in other words, the cardiovascular risk increases as the uric acid elevates in blood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hyperuricemia is a pathological entity that is characterized by blood uric acid values beyond upper limits that has been largely associated with metabolic syndrome and increased cardiovascular risk [8][9][10]. In this sense, a recent study conducted in 22,983 Chinese adults demonstrated that subjects with hyperuricemia had higher prevalence of cardiovascular risk factors, such as dyslipidemia, hypertension, and type 2 diabetes (T2D), than individuals with normal uric acid values [11]. It is also worth mentioning that uric acid concentration associated directly with the number of cardiovascular risk factors; in other words, the cardiovascular risk increases as the uric acid elevates in blood.…”
Section: Introductionmentioning
confidence: 99%
“…The association of hyperuricemia with cardiovascular diseases is accompanied by a low-grade inflammation state that is characterized by increased proinflammatory activation of macrophages [11,12]. In this regard, the exposure of ApoE −/− mice to allopurinol (an inhibitor of uric acid production) does not only reduce atherosclerotic plaque size, but also macrophage infiltration and the expression of tumor necrosis factor-alpha (TNF-alpha) and interleukin (IL-) 1 beta, both typical proinflammatory cytokines [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that age [12][13][14][15][16], hypertension [4,17], obesity [18,19], hyperuricaemia [20][21][22][23][24], dyslipidaemia [25] are all risk factors for CVD. Although the above results were obtained in the general population, these risk factors remain as predictors in the risk model established in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As widely accepted in previous studies [6,[24][25][26], hyperuricemia was defined as SUA ≥ 7 mg/dL for men or SUA ≥ 6 mg/dL for women.…”
Section: Diagnosis Of Hyperuricemiamentioning
confidence: 99%